MNGI-15. RARE PRESENTATION OF EXTRACRANIAL PARAVERTEBRAL MENINGIOMA IN A CHILD WITH NEUROFIBROMATOSIS TYPE 2: A CASE REPORT. (5th November 2018) - Oberoi, Sapna; Leitao, Darren; Stefanovici, Camelia; Del-bigio, Marc; Higgins, Rick; Bunge, Martin; Serleitis, Demitre; Vanan, Magimairajan Issai
Abstract: Meningioma is a rare intracranial tumor of children and adolescents. Meningioma occurring outside the central nervous system is even rarer. We describe an 11- year old child who presented with extracranial paravertebral skull base meningioma and left vestibular schwannoma with an underlying neurofibromatosis type 2 (NF2). The patient presented with hearing loss, painless left neck mass and right sided horner syndrome. A CT scan and MRI revealed a skull base tumor in the region of the left carotid body encasing the vessels, opacifying the left middle ear cavity, extending intracranially through the left jugular foramen along with regional lymphadenopathy and left vestibular schwannoma. MRI spine identified Arnold-Chiari I malformation and two extramedullary enhancing lesions (1-2cms) at the level of thoracic spine. With a differential diagnosis of sarcoma and peripheral never sheath tumor with metastasis to spinal cord, partial excision of the skull-base tumor was performed along with suprahyoid neck dissection. Bone marrow examination to rule out metastasis was normal. Pathology confirmed the diagnosis of meningioma (meningothelial variant, WHO grade-1). Lymph nodes showed reactive hyperplasia. With this clinical presentation of hearing loss, extracranial meningioma, vestibular schwannoma and spinal tumour likely to be spinal meningioma or schwannoma, a diagnosis of NF2 was suspected. Next generation sequencing showed deletion of exon 4 in NF2 gene. On further screening, early changes of cataract were seen in the right eye. Surgery couldn't be done for treatment of meningioma due to the encasement of the vital structures. Therapy with bevacizumab and everolimus was started to improve hearing loss secondary to schwannoma and extracranial meningioma. This report highlights the uncommon presentation of NF-2 and extracranial meningioma. Extracranial meningioma must be considered in the differential diagnosis in a child presenting with tumor of the skull base, middle ear and neck.